Bush encroachment in sub-Saharan Africa: causes, impacts, and management strategies - A review - Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
presentation about Bush encroachment that poses a pervasive challenge to Sub-Saharan Africa's rangelands, impacting ecosystem dynamics, biodiversity, and local livelihoods. This study comprehensively analyzes bush encroachment in the region, exploring its causes, impacts, and management strategies. Climate change, driven by global factors like fossil fuel combustion and deforestation, intensifies the greenhouse effect, contributing to encroachment. Land use practices, such as overgrazing and invasive species, further spur woody vegetation expansion. Encroachment adversely affects biodiversity, reducing plant diversity and altering habitat composition, impacting various ecosystem components. Livestock production faces challenges due to decreased forage availability, impacting rangeland sustainability. Water resources are also affected, with increased tree cover leading to higher water consumption. Management strategies include prescribed burning, rotational grazing, selective tree removal, and reseeding with desirable grass species. Integrated land management approaches are crucial, combining ecological restoration with sustainable livestock production to restore ecosystem functionality and support local communities. Collaborative efforts among policymakers, land managers, and communities, informed by science-based strategies and local knowledge, are essential for effective bush encroachment management in Sub-Saharan Africa.